The Gnostic heritage of Heavy Metal. Issue 3 (2nd July 2016) - Belgrad, Daniel
Abstract: The religious impulse in early Heavy Metal music is fundamentally Gnostic. An ancient religious tradition emphasising the rule of evil and the remoteness of salvation, Gnosticism was integrated into hard rock music in the late 1960s. Early Heavy Metal musicians encountered Gnosticism as it had been absorbed into popular fiction and film, including especially the works of Dennis Wheatley and J.R.R. Tolkien. Prominent in giving Gnosticism musical form was the band Black Sabbath, whose first three albums in 1970 and 1971 pioneered the patterns of musical practice that would become the conventions of the genre. Heavy Metal's alternately heavy and giddy affect, created via a synthesis of musical practices and complementary verbal and visual representations, brought Gnostic beliefs into meaningful intersection with the everyday lives of young blue-collar males in Britain and the United States, as they confronted the post-industrial age in the context of a waning sixties counterculture.